Efek Minuman Keras Oplosan terhadap Perubahan Histopatologi Organ Renal Tikus Wistar Jantan - Made Masagung Kawiartha; Rena Normasari; Bagus Hermansyah (Pustaka Kesehatan, 2018)
Mixed liquor is a liquor mixed with other substances, mainly ethanol and methanol. Mixed liquor can cause kidney destruction. The aim of this study was to investigate the effect of mixed liquor toward kidney's microscopic and macroscopically changes. This study used 24 rats which were divided into 4 groups consist of 1 control group and 3 experimental groups. The first, second, and third experimental groups were given ethanol 1,296ml/2 days; methanol 0,2592ml/2days and aquades 1,4448ml/2 days for 5 days; 11 days and 17 days, respectively. Afterward rats were terminated and the right kidney mass was measured. The kidney tissue was prepared for histological examination and the number of necrotic cell was calculated. According to Kruskal Wallis test, kidney mass was not significantly different (p>α) while total necrotic cells was significantly different (p<α). This study showed that rats induced with mixed liquor for 5 , 11, and 17 days resulted in kidney microscopically change.